Exploring the effects of impression management; individualistic/collectivistic orientations; risk taking and time orientation on variety seeking : a cultural perspective. - Chew, Siew Hwee. (2008)
The research objective is to propose and test possible differences for VS in divergent cultures. Literature suggests that VS can be driven both intrinsically (e.g. need for uniqueness or affiliation) and extrinsically (e.g. different purchasing contexts). However, some of these drivers may be culturally-bound.